Chalcone T4 Inhibits RANKL-Induced Osteoclastogenesis and Stimulates Osteogenesis In Vitro - de Matos, Iolanda Augusta Fernandes [UNESP]; Fernandes, Natalie Aparecida Rodrigues [UNESP]; Cirelli, Giovani [UNESP]; de Godoi, Mariely Araújo [UNESP]; de Assis, Letícia Ribeiro [UNESP]; Regasini, Luis Octávio [UNESP]; Rossa Junior, Carlos [UNESP]; Guimarães-Stabili, Morgana Rodrigues [UNESP] (MDPI, 2023)
Chalcones are phenolic compounds produced during the biosynthesis of flavonoids that have numerous biological activities, including anti-inflammatory, antioxidant and anticancer. In this in vitro study, we investigate a newly synthesized chalcone (Chalcone T4) in the context of bone turnover, specifically on the modulation of osteoclast differentiation and activity and osteoblast differentiation. Murine macrophages (RAW 264.7) and pre-osteoblasts (MC3T3-E1) were used as models of osteoclasts and osteoblasts, respectively. Differentiation and activity osteoclasts were induced by RANKL in the presence and absence of non-cytotoxic concentrations of Chalcone T4, added in different periods during osteoclastogenesis. Osteoclast differentiation and activity were assessed by actin ring formation and resorption pit assay, respectively. Expression of osteoclast-specific markers (Nfatc1, Oscar, Acp5, Mmp-9 and Ctsk) was determined by RT-qPCR, and the activation status of relevant intracellular signaling pathways (MAPK, AKT and NF-kB) by Western blot. Osteoblast differentiation and activity was induced by osteogenic culture medium in the presence and absence of the same concentrations of Chalcone T4. Outcomes assessed were the formation of mineralization nodules via alizarin red staining and the expression of osteoblast-related genes (Alp e Runx2) by RT-qPCR. Chalcone T4 reduced RANKL-induced osteoclast differentiation and activity, suppressed Oscar, Acp5 and Mmp-9 expression, and decreased ERK and AKT activation in a dose-dependent manner. Nfact1 expression and NF-kB phosphorylation were not modulated by the compound. Mineralized matrix formation and the expression of Alp and Runx2 by MC3T3-E1 cells were markedly stimulated by Chalcone T4. Collectively, these results demonstrate that Chalcone T4 inhibits in osteoclast differentiation and activity and stimulates osteogenesis, which indicates a promising therapeutic potential in osteolytic diseases.
Keywords: chalcone; intracellular signaling; osteoclastogenesis; osteogenesis